Studying ABI3 variant immune contributions to Alzheimer's disease in a transgenic mouse model: Developing topics. (7th December 2020) - Liang, Xinyan
Abstract: Background: Alzheimer's Disease (AD) is a progressive disorder populating in a world‐wide range, which causes dementia with accumulation of amyloid‐beta (Aβ) and hyperphosphorylated tau. AD destroys memory and disrupts cognition, as well as impairs thinking, behaving and person's ability to function independently. Numbers of genes now have been confirmed through large scale genetic studies as significant AD risk genes, including ABI3. Abelson interactor (ABI) family is an adaptor protein family commonly participating in regulation of actin cytoskeleton in cell. As a member of ABI family, ABI3 can modulate cell motility process like inhibiting tumor metastasis and migration. Genetic variants of ABI3 have been found to be strongly associated with late onset AD (LOAD) in various human populations, but the molecular mechanisms of how they influence AD pathogenesis remain unknown. Method: In order to further study the pathological mechanisms of ABI3 in AD in vivo, we created an Abi3 transgenic mouse model on C57BL/6 background carrying a human ABI3 mutation (S209F) by CRISPER/Cas‐mediated genome engineering. ABI3 S209F mutation is encoded by a very rare variant rs616338 (MAF=0.008, OR = 1.43 for AD with P = 4.56 × 10 −10 ). In this transgenic model, a corresponding mouse S212F mutation was introduced into Exon 5 on Chromosome 11 by homology‐directed repair, and homozygous Abi3 F/F mice were generated by crossing the F1 heterozygotes. In addition, we also crossed Abi3 F/F with the 5xFAD model of AD to determine the influence of this ABI3 mutation on AD pathology and cognitive functions in vivo . Result: We hypotheses 5xFAD mice who carrying the ABI3 mutation may exhibit exacerbated AD pathologies compared with 5xFAD with wildtype ABI3, including accelerate Aβ aggregation and neuroinflammation. As ABI3 is exclusively expressed in immune cells in the brain and peripheral, this new Abi3 F/F model will be an effective method for us to understand the immune contribution in AD pathogenesis and perhaps the crosstalk between peripheral and central in the disease as well. Conclusion: We believe that studying AD with ABI3 Tg mouse models can allow us to have better understanding on the immune contribution to AD pathogenesis and provide valuable strategies on clinical therapy.